2012
DOI: 10.3892/ol.2012.803
|View full text |Cite
|
Sign up to set email alerts
|

The role of AIB1 in breast cancer

Abstract: Abstract. Amplified in breast cancer 1 (AIB1) is a member of the p160 steroid receptor coactivator family that mediates the transcriptional activities of nuclear receptors including estrogen receptor (ER) and progesterone receptor (PR), as well as certain other transcription factors, including E2F1 and p53. AIB1 is widely implicated in nuclear receptor-mediated diseases, particularly malignant diseases, including breast, prostate, gastric and pancreatic cancers. AIB1 was initially implicated in hormone-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…Interestingly, we showed that a number of the AR coregulators were AR regulated and that enhanced expression of a subset of these coregulators was observed in castration-challenged PC cells ectopically overexpressing AR (Urbanucci et al 2008). Among the androgen-regulated coregulators identified were amplified in breast cancer 1 (AIB1) and CBP, both HATs which have been shown to increase nuclear receptors' activities and are implicated in mechanisms of drug resistance (Chang & Wu 2012, Culig 2016, Jin et al 2017.…”
Section: The Androgen Receptor Drives Chromatin Relaxation As An Oncomentioning
confidence: 99%
“…Interestingly, we showed that a number of the AR coregulators were AR regulated and that enhanced expression of a subset of these coregulators was observed in castration-challenged PC cells ectopically overexpressing AR (Urbanucci et al 2008). Among the androgen-regulated coregulators identified were amplified in breast cancer 1 (AIB1) and CBP, both HATs which have been shown to increase nuclear receptors' activities and are implicated in mechanisms of drug resistance (Chang & Wu 2012, Culig 2016, Jin et al 2017.…”
Section: The Androgen Receptor Drives Chromatin Relaxation As An Oncomentioning
confidence: 99%
“…Likewise, PTTG stimulates fibroblast growth factor 2 (FGF2) and vascular endothelial growth factor (VEGF) production, accelerates tissue angiogenesis, and facilitates pituitary tumor progression through local invasion of the surrounding tissues [ 99 , 102 ]. On the other hand, AIB1, an important factor in the development of breast cancer [ 103 ], is overexpressed by the action of 17-β-estradiol [ 104 ], and AIB1 may be an important diagnostic and therapeutic target in breast cancer [ 105 ]. The relation between ERα and AIB1 is well established [ 103 , 106 , 107 ], and the over-expression of AIB1 could be related to the increases in the incidence of pituitary tumors in mice [ 108 ].…”
Section: Estrogenic Receptors Prolactinomas and Aib1mentioning
confidence: 99%
“…On the other hand, AIB1, an important factor in the development of breast cancer [ 103 ], is overexpressed by the action of 17-β-estradiol [ 104 ], and AIB1 may be an important diagnostic and therapeutic target in breast cancer [ 105 ]. The relation between ERα and AIB1 is well established [ 103 , 106 , 107 ], and the over-expression of AIB1 could be related to the increases in the incidence of pituitary tumors in mice [ 108 ].…”
Section: Estrogenic Receptors Prolactinomas and Aib1mentioning
confidence: 99%
“…The overexpression of SRC-3 was reported to induce tumorigenesis and chemoresistance by modulating cancer-related signaling pathways, accelerating G1/S cycle transition, promoting the expression of anti-apoptotic proteins and inhibiting the expression of pro-apoptotic proteins (Ma et al, 2011;Oh et al, 2004). The interaction between SRC-3 and histone acetyltransferases (HATs) and histone deacetylases (HDACs) alter the acetylation of histones and influence the transcription of genes (Chang and Wu, 2012). Effective SRC-3 inhibitors have been proposed as a promising therapeutic strategy for these tumors (Tien and Xu, 2012).…”
Section: Introductionmentioning
confidence: 99%